Sustainable Development: Implementation of The Talqin Method In Memorizing The Quran - Ikhwan Rahman; M. Yakub Iskandar; Martin Kustati; Nana Sepriyanti (STKIP Pesisir Selatan, 2024)
The Quran is the holy book of Muslims which has a central role in human spiritual and moral life. Memorizing the Quran is a form of noble practice recommended by the Prophet Muhammad. Various methods have been developed to help the process of memorizing the Quran, one that has been proven effective for centuries is the Talqin method. This research aims to examine the implementation of the Talqin method in memorizing the Koran. The research method used is Systematic Literature Review (SLR) by analyzing 30 reputable journals published over the last five years (2019-2024). Data sources were obtained from scientific databases such as Google Scholar, ScienceDirect, Scopus and DOAJ. The findings show that the Talqin method has proven effective in helping students memorize the Quran quickly and accurately. This method has also been proven to increase students' understanding of the meaning of the Koran and build strong relationships between teachers and students. This can be seen in the factors that support the successful implementation of the Talqin method such as; teacher skills, student motivation, conducive learning environment. However, there are several challenges that need to be considered in its implementation, such as the time required, teacher availability, facilities and infrastructure. It is hoped that this research can provide a valuable contribution to the development of Islamic education practices and tahfidz of the Quran, so that it can produce a generation of Qur'anists who have noble character and love the Quran.